The Analysis of the Factors Related to the Quality of Work Life of the Workers at PT. Semen Indonesia Tuban Factory - Rachmawati Maulidhina (Universitas Airlangga, 2019)
Introduction: Quality of work life (QWL) is an essential concept related to the life of a worker. QWL is made to realize the balance between the workers’ needs and interests and the workload to ensure work satisfaction as well as the organization’s productivity. PT. Semen Indonesia is the biggest cement producing company in Java Island. The company manages the human resources to achieve job satisfaction by carrying out QWL programs. The aim of this research is to analyze the factors related to QWL that can lead to the workers’ QWL, especially to the packers and loader workers at PT. Semen Indonesia Tuban Factory. Methods: This research is completed by implementing the cross-sectional design with a qualitative approach. The population of this research is all workers in the packer and loader department Tuban IVth plant, as many as 80 people, while the sample consists of 45 workers chosen by the simple random sampling method. Seven identified factors from the literature review are the workers’ involvement, balanced compensations, a sense of security towards the work, occupational safety and health, career development, work relationships, and a sense of pride in the company. Results: Indicate that there are significant and positive relationships between all seven factors and the QWL. Conclusioan: that developing a non-financial compensation, socializing career development programs, and job guarantee will lead to job satisfaction and to ensure the organization’s productivity. Keywords: job satisfaction, packers and loaders, productivity, quality of work life